Visual research methodologies, branding and magazine readerships. Issue 3 (11th July 2016) - Trigoni, Mirsini
Abstract : Purpose: – The purpose of this paper is to explore how interior spaces can be differently represented across home magazines of different background and target audiences. And investigates how visual texts can differentiate a brand, increase brand loyalty and target different market segments. Design/methodology/approach: – This paper draws on material for comparative analysis from three home magazines ( Wallpaper, Ideal Home and Elle Decoration ). It combines quantitative methods (content analysis) and qualitative methods (fieldwork observations). Findings: – This research suggests that Wallpaper is not just a magazine, but it has expanded to become a brand with a well-recognized logo. Practitioners managed to create a strong brand through the creation of a magazine with a very distinctive style among its competitors that clearly address the elite. Research limitations/implications: – This paper focused on the production of magazine features and representations of interior spaces. Further research could be conducted to explore how readers belonging to different economic, social and cultural groups "receive" and comprehend the home magazine features. Practical implications: – The findings of this research could be used to analyse fashion photography in editorial, fashion advertising, fashion brand websites and social media, thereby assisting in the analysis of fashion photography and the relationship between fashion items, set design, styling of space, target audiences, branding and visual communication; exploring further how fashion photography can effectively target different market segments and enhance a fashion brand and its identity. Originality/value: – The area of magazine features, photography, set design and styling of space has received limited attention from scholars. The method of analysing interior spaces/set design presented in this paper can be developed further to provide in depth analysis of window and in store display design and the use of display design and visual merchandising as a way to reflect the fashion brand identity, target-specific market segments, differentiate and gain competitive advantage.